(untitled) (International Journal of Architecture and Urbanism, 2025)
The structure supported by foundation with different elevations, which the foundation is supported at different elevations, is one of the most commonly used structural types in hillside buildings. In this structure, the uneven settlement of the foundation generates internal forces in the structure. In this paper, the effect of foundation uneven settlement on the internal force of the structure in a hillside building is analyzed. The results showed that even small uneven settlements also can generate large internal forces in the structure, while internal forces mainly occur in the beams connecting the upper and lower support storey, and relatively large internal forces occur in the supporting columns of upper embedding storey. When the uneven settlement occurs, the beam mainly generates shear and bending moments and the axial force is relatively small. The column mainly generates axial and bending moments, and tensile internal force is occurred in the some beams. The results obtained in this paper can be referred to the structural design of the hillside building structure and serve as a basis for further research.